Detection of AI Utilization in Language Learning: A Study on the Implementation of Chat Gpt In Academic Writing Among Indonesian Higher Education Students - Iskandar; Syekh Adiwijaya Latief; Muh Arief Muhsin; Nurul Izzatil Hasanah (South Sulawesi Education Development (SSED), 2024)
The integration of artificial intelligence (AI) technologies in educational settings has become increasingly prevalent, particularly in the realm of language learning In English context. This study aims to investigate the utilization of ChatGPT, an AI-powered conversational agent, in enhancing academic writing skills among Indonesian higher education students, specifically in the context of English language learning. Through a mixed-methods approach, including surveys and qualitative analysis of student writings, this research explores the effectiveness and impact of ChatGPT in assisting students with their academic writing tasks. he research findings indicate that ChatGPT is predominantly utilized in completing academic tasks, particularly in composing scholarly papers. Furthermore, Chat GPT is perceived as user-friendly with a high level of accuracy in locating relevant literature for assignments. The findings of this study contribute to the growing body of literature on AI integration in education and provide insights into the practical implications of using Chat GPT as a learning tool in English language education